Health care help seeking behaviour among prisoners in Norway - Nesset, Merete Berg (BioMed Central, 2011)
BACKGROUND: Prisoners are associated with high health care needs compared with the general population. This study aims to investigate prisoners' use of health service. METHODS: A cross-sectional study of 29 prisons in central and southern parts of Norway. A questionnaire was distributed to 1, 454 prisoners (90% response rate). Multilevel analyses were employed to analyse help seeking behaviour among the prisoners. RESULTS: Help seeking was substantially associated with sleep problems and drug problems. There was also a tendency for closed prisons as well as high staffing levels of healthcare professionals to be associated with elevated health care use. CONCLUSIONS: This study suggests that sleep problems and drug use are most frequently associated with health service use. The differences in health care use between prisons suggest that the implementation of prison health care standards should be addressed.